PENGENAL WAJAH REAL TIME BERBIAYA RENDAH MENGGUNAKAN FPGA DIGILENT PYNQ-Z1 DENGAN METODE PCA - Arief Ainur Rafiq; Pujono Pujono; Eka Dyah Puspitasari (Jurusan Teknik Elektro, Universitas Bangka Belitung, 2019)
Nowadays, face recognition plays central role in monitoring, biometric, and security fields. This paper presents FPGA (Field Programmable Gate Array) using real-time architecture basis. It costs less for face recognition. The face recognition module recognizes faces that have been detected by video and then the data are processed by using eigenface or Principal Component Analysis (PCA) algorithm. The architecture is implemented in FDGA Digilent Pynq-Z1, while the proposed architecture is part of the system that can recognize faces in crowd with series of faces that have been set before. In the implementation, this system can be integrated in the real-time monitoring system in crowd (such as airport, bus station, railway station, and port) to identify threat source. It is hoped that it can also decrease the criminal activity.